ANALISIS FUNGSI DAN MAKNA METAFORA DALAM NOVEL TENUN BIRU KARYA UGI AGUSTONO: KAJIAN STILISTIKA - Desy Ningsih Komalasari; Zulkifli Zulkifli; Ahmadin Ahmadin; Didit Haryadi (Universitas Batanghari, 2025)
Problem in this research is on a metaphor in a novel Tenun Biru work Ugi Agustono: a stylistic study. Problem of this research are focused on investigating the form, function and meaning of metaphors found in a novel Tenun Biru. There are two benefits of this research namely theoretical and practical benefits and this research use a qualitative method as well as descriptive method. This research using the theory of stylistic pertaining to style of language (figure) to get better results in analyzing form, function and meaning metaphor, as of theory of stylistic considered relevant to inspect figure of a metaphor in a novel. Thus this research get the result of a metaphor comprising a antropormorfic metaphor, sinestic metaphor, abstract into concrete metaphor, dead metaphor, and the life metaphor. This study aims to examine the function and meaning of metaphors in the novel Tenun Biru. Consequently, this research provides both theoretical and practical benefits by employing a qualitative research method with a descriptive approach. The study utilizes stylistic theory, which relates to language style (figurative language), to achieve better results in analyzing the forms, functions, and meanings of metaphors. Stylistic theory is considered relevant for studying metaphors in the novel. Furthermore, the functions and meanings of metaphors include informational, expressive, directive, and phatic functions and meanings. Thus, this research identifies the functions and meanings of metaphors used by the author in crafting a literary work in the form of a novel, as metaphors are employed as comparisons to analogize events that serve as the focus of this study.